2016
DOI: 10.1038/ncomms13169
|View full text |Cite
|
Sign up to set email alerts
|

A metal-organic cage incorporating multiple light harvesting and catalytic centres for photochemical hydrogen production

Abstract: Photocatalytic water splitting is a natural but challenging chemical way of harnessing renewable solar power to generate clean hydrogen energy. Here we report a potential hydrogen-evolving photochemical molecular device based on a self-assembled ruthenium–palladium heterometallic coordination cage, incorporating multiple photo- and catalytic metal centres. The photophysical properties are investigated by absorption/emission spectroscopy, electrochemical measurements and preliminary DFT calculations and the ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
117
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(129 citation statements)
references
References 55 publications
6
117
0
1
Order By: Relevance
“…As we can see, the H 2 evolution of MOC‐16 without TTF shows a production rate of 129 μmol h −1 in the initial 3 h, but drops obviously in the following procedure. A total H 2 production of 1597 μmol is reached after 47 h, representing a turnover number (TON) of 605 (based on Pd 2+ catalytic centers, 2.64 μmol) which is comparative with our previous study (TON=635 in 48 h) conducted in a 100 mL DMSO–H 2 O solution with successive 3 h recycling procedure . In the presence of TTF, the H 2 production capacity is overall improved, but the evolution rates show close dependence on the amount of TTF.…”
Section: Figuresupporting
confidence: 56%
See 2 more Smart Citations
“…As we can see, the H 2 evolution of MOC‐16 without TTF shows a production rate of 129 μmol h −1 in the initial 3 h, but drops obviously in the following procedure. A total H 2 production of 1597 μmol is reached after 47 h, representing a turnover number (TON) of 605 (based on Pd 2+ catalytic centers, 2.64 μmol) which is comparative with our previous study (TON=635 in 48 h) conducted in a 100 mL DMSO–H 2 O solution with successive 3 h recycling procedure . In the presence of TTF, the H 2 production capacity is overall improved, but the evolution rates show close dependence on the amount of TTF.…”
Section: Figuresupporting
confidence: 56%
“…Along this line, synthetic strategies have been reported to engineer functional coordination innerspace of nanocages via incorporation of either redox‐active or photoactive centers, thus generating MOC‐based photocatalytic host–guest systems to imitate natural photosynthesis, where the spatially separated electron and/or energy transfer processes can facilitate photocatalytic water/H 2 S splitting, as well as other chemical transformations. To achieve efficient conversion from solar energy to chemical energy in such host–guest systems, one of the fundamental factors is to control the photo‐induced redox events in the confined chemical nanospace .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In this circumstance, to pursue a high‐efficiency photocatalytic system, suitable band alignment and panchromatic absorption behavior of the light harvester appear to be major concerns. Accordingly, a variety of semiconductor materials have been developed as available candidates for photocatalysis, including traditional alternatives such as metal oxides (e.g., TiO 2 , perovskite oxides), metal sulfides, C 3 N 4 , carbons, metal organic frameworks . Morover, our group for the first time has reported that the CsPbBr 3 quantum dot, a representative lead halide perovskite material, was able to conduct the photocatalytic reduction of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic polyhedra (MOPs) as crystalline coordination materials that are constituted by metal ions and organic ligands . Owing to their unique features, such as permanent porosity and unsaturated metal centers, MOPs have shown great potential for applications in drug delivery, gas adsorption and storage, chemical sensors, and catalysis . As a common ligand isophthalic acid and its corresponding derivatized ligands have been widely used to prepare MOP materials .…”
Section: Introductionmentioning
confidence: 99%